Assessing the Environmental Impacts of the Industrial Park in Kabul City - Sahak, Kawoon; Mushwani, Hayatullah (Journal of Natural Sciences – Kabul University, 2025)
Industrial activities have caused various environmental problems in Kabul city. To assess the environmental impacts in Kabul’s industrial park, this research study was conducted. Twenty factories were selected, and information was collected using a valid questionnaire containing questions related to safety systems, product types, and policies and guidelines. The results indicate that factories such as those producing plastics, pharmaceuticals, detergents, and iron operate in Kabul Industrial Park. Most of the raw materials used in these factories are imported, and hydropower electricity is used for their operation. To minimize adverse environmental effects, factories should implement national and international standards and regularly monitor their operations to ensure that the environmental impacts are within the acceptable range.